NSC KIPT accelerator on nuclear and high energy physics - Dovbnya, A.N.; Guk, I.S.; Kononenko, S.G.; van der Wiel, M.; Botman, J.I.M.; Tarasenko, A.S. (Вопросы атомной науки и техники, 2004)
Qualitatively new level can be performed by creating the accelerator that will incorporate the latest technological achievements in the field of electron beam acceleration on the basis of a superconducting TESLA accelerating structure. This structure permits the production of both quasi-continuous polarized electron beams required for ingenious experiments to verify current theoretical models of nuclear matter interaction, and supershort pulsed beams of electrons with a high current for studies into FEL and neutron physics.